The Association of CSF sTREM2 With Cognitive Decline and Its Dynamic Change in Parkinson's Disease: Analysis of the PPMI Cohort - Qin, Qixiong; Wan, Hengming; Wang, Danlei; Li, Jingyi; Qu, Yi; Zhao, Jingwei; Li, Jiangting; Xue, Zheng (Frontiers in Aging Neuroscience, 2022)
Background: Soluble fragments of triggering receptor expressed on myeloid cells 2 (sTREM2) in cerebrospinal fluid (CSF) is a biomarker of microglial activation and increased in several neurodegenerative diseases. However, the role of sTREM2 in Parkinson’s diseases (PD) remains unclear. This study aims to investigated whether CSF sTREM2 are changed during the pathology of PD and its association with cognitive decline. Methods: We recruited 219 de novo PD patients and 100 healthy controls from Parkinson’s Progression Markers Initiative (PPMI). Cross-sectional and longitudinal associations between cognition and CSF sTREM2 were evaluated using multivariable-adjusted models. To assess the changes of CSF sTREM2 during the pathology of PD, patients were classified through the A/T classification framework with addition of α-synuclein (α-syn), which we implemented based on the CSF Amyloid β-peptide 1-42 (A) and phosphorylated tau (T) and α-syn (S). Results: CSF sTREM2 did not differ between healthy controls and PD patients or between PD clinical subgroups (p > 0.05). However, higher baseline CSF sTREM2 predicted greater global cognitive decline in PD patients (β = -0.585，p = 0.039). Moreover, after a mean follow-up of 5.51±1.31 years, baseline CSF sTREM2 that elevated in the middle tertile (HR = 2.426, 95% CI: 1.023-5.754, p = 0.044) and highest tertile (HR = 2.833, 95% CI: 1.226-6.547, p =0.015) were associated with a future high risk of cognitive decline. Additionally, CSF sTREM2 decreased in abnormal Aβ pathology (A+) and α-syn pathology (S+) but normal tau pathology, while increased in abnormal phosphorylated tau (T+) (p < 0.05). Conclusion: CSF sTREM2 may be a promising predictor for the cognitive decline in PD rather than a diagnostic biomarker. The dynamic change of CSF sTREM2 in PD may help to the monitor of neuronal injury and microglial activity.